Stochastic Production Frontier Analysis and Technical Efficiency of Yellow Yam (Dioscorea cayenensis) Farmers in Orhiowmon Local Government Area of Edo State, Nigeria - Eweka, Kayode Israel; Egbodion, John; Osaherunwmen, Samuel (Direct Research Journal of Agriculture and Food Science, 2024)
Yellow yam has both socio-cultural and traditional values in the life of the people in Orhionmwon local government area. This study applied the stochastic production frontier analysis to measure the technical efficiency of yellow yam producers, the Cobb Douglas functional form was used to estimate the technical efficiency.  Two-stage sampling technique was used in selecting (100) yellow yam farmers for the study. Primary data was collected directly from the field using structured questionnaire with open and close ended questions. Descriptive and inferential statistics was used for data analysis.  The study showed majority of respondents constituting 69% of the population, were males. The SPF estimates reveals that yam setts and staking materials positively and significantly influenced the output of yellow yam production at (P
Keywords: Yellow yam; stochastic production frontier; Technical efficiency